(untitled) (Huellas, 2025)
The main objective of this research is the analysis of territorial transformations in the peri-urban area of Villa Mercedes. Through an interdisciplinary and historical approach, this study sought to understand how land use has evolved in these areas over time. To achieve this, satellite imagery, in-depth interviews, and institutional and personal archives were used to analyze the reduction in horticulture and cattle raising in the light of an expanding urban area and specific socio-economic processes. Among the findings, it was determined that the disorganized expansion of the urban plant has disarticulated the irrigation system, significantly compromising agricultural production in peri-urban areas. As a result of the provincial economic change and driven by the industrial boom, “quintas” families abandoned horticultural, as well as dairy production. It was found that dependence on an unstable irrigation system, vulnerable to climatic phenomena, has limited the productive stability of “quinta” families, generating uncertainty and resulting in one of the causes of land abandonment. This process was facilitated by a weak institutional framework and limited authority of the irrigation commissions.